On the spectrum of Cayley graphs - Ghorbani, M.; Songhori, M. (Algebra and Discrete Mathematics, 2020)
The set of eigenvalues of the adjacency matrix of a graph is called the spectrum of it. In the present paper, we introduce the spectrum of Cayley graphs of order pqr in terms of character table, where p, q, r are prime numbers. We also, stablish some properties of Cayley graphs of non-abelian groups with a normal symmetric connected subset.